Building Financial Awareness and Personal Branding: Strategies to Avoid Riba and High-Risk Online Transactions - Sholahuddin, Muhammad; Nasir, Moechamad; Bawono, Andy Dwi Bayu; Permatasari, Qisthoni; Annisa, Widya (Pascasarjana Universitas Mataram, 2024)
In the face of increasing financial complexities and digital transaction risks, a workshop and mentoring program was conducted by Universitas Muhammadiyah Surakarta (UMS) in collaboration with MSU, PCIM-PCIA Malaysia, and PRIM-PRIA Malaysia to enhance financial literacy, personal branding skills, and awareness of secure online transactions. Engaging 38 participants, the program utilized an interactive learning model—comprising pre-tests, visual presentations, case simulations, group discussions, and post-tests—to cover topics such as professional identity building, Islamic financial principles to avoid riba, and strategies to counter digital fraud. The pre-test results revealed an average score of 53.2, indicating a low-to-moderate understanding, while the post-test results showed significant improvement, with an average score of 82.1. Participants demonstrated improved abilities in identifying online transaction risks, recognizing forms of riba, and applying strategic personal branding techniques. This initiative effectively addressed critical challenges in financial literacy and digital security, while also offering a replicable educational model. The outcomes contribute to fostering financially aware, digitally secure, and professionally resilient individuals, equipping them to thrive in a globalized economic and digital environment